Self-Healing Supramolecular Hydrogels for Tissue Engineering Applications - Saunders, Laura (Macromol Biosci, 2018)
Self-healing supramolecular hydrogels have emerged as a novel class of biomaterials that combines hydrogels with supramolecular chemistry to develop highly functional biomaterials with advantages including native tissue mimicry, biocompatibility, and injectability. These properties are endowed by the reversibly cross-linked polymer network of the hydrogel. These hydrogels have great potential for realizing yet to be clinically translated tissue engineering therapies. This review presents methods of self-healing supramolecular hydrogel formation and their uses in tissue engineering as well as future perspectives.